The impulsiveness of gen Z buyers. a study of buy-now-pau-later services - Chan, Khai Yee (2023)
Regarding impulse buying things, "buy now, pay later" services, and other behaviours, Gen Z demonstrates a number of traits and tendencies. Since they were raised in the digital era, members of Generation Z are more inclined to make impulsive purchases. This study intends to investigate how the five-factor personality model affects the adoption of "buy now, pay later" services and impulsive purchase behaviour among Generation Z. 309 replies from a Malaysian online poll were included in the study. In order to assess 309 sets of data that moderated the influence of the five-factor personality model on Generation Z's impulse buying behaviour and use of "buy now, pay later" services, this study used the Smart Partial Least Squares (SmartPLS). The results of this study realize the valuable influence of the independent variables, namely Extraversion, Conscientiousness, Openness, Agreeableness and Neuroticism have a significant impact on Generation Z’s impulse buying behaviour and “buy now, pay later” service usage. This study provides researchers with an interactive approach to assess psychological, and social moderating influences on technology adoption. It can also help practitioners identify important factors that influence consumers’ impulse consumption, thereby further influencing consumers’ willingness to adopt BNPL services in the analysis report. The novelty of this study is tested through the theoretical variables of the five-factor personality model, explains consumers' impulse consumption and intention to adopt BNPL services that are limited by the adopted theory, and makes further suggestions for supplementing the variance.